Social dynamics fuelling the spread of HIV/AIDS in the Free State: implications for prevention, care, treatment and support - Redelinghuys, Nola (Acta Academica: Critical views on society, culture and politics, 2006)
This article examines some of the socio-economic and socio-cultural factors that may have shaped a social context conducive to the spread of HIV/AIDS in the Free State. Among the factors identified driving the spread of the disease in this province, low levels of socio-economic development, population mobility, and gender inequality are paramount. The article further reasons that the successful implementation of strategies aimed at HIV prevention, treatment and care, such as the Comprehensive Plan of 2003, hinges on the social context enhancing or inhibiting the implementation thereof. Lastly, it is reasoned that the issues of planning and strategy development for the prevention of HIV/AIDS should slot into broader social policy and planning at the national and provincial levels. Amongst others, this would include policy and planning that target those socio-economic and socio-cultural forces which are fuelling the spread of the disease.